MODALITIES OF LOCAL DEBT ANALYSIS IN THE NORTH-WEST REGION OF ROMANIA - Ioan BĂTRÂNCEA; Lucian GĂBAN; Liviu BECHIŞ (USV Annals of Economics and Public Administration, 2016)
Public debt is a topic of great interest, problem tracked over the years and has worsened with the outbreak of the second wave of financial crisis around the world, namely the sovereign debt crisis . Among the countries affected by this phenomenon are, along with countries like Greece, Italy, Spain and Portugal, our country whose public debt has doubled in the past four years and will affect future regional development in Romania. In late 2010, the Romanian government debt (according to ESA 95 methodology) reached 31.02 % of GDP. Although this indicator falls comfortably within the 60 % of GDP Maastricht Treaty, its growth rate remains worrying. In 2012 there was a level of government debt ( EU methodology - ESC 95 ) 37.8 % of GDP, and for 2013 the estimated level of government debt is below 36.4 % of GDP ( 51 billion euro) ranging is below the Maastricht Treaty provided for 60% of GDP, an advantage for Romania , given the new rules on public debt and budget deficit introduced by the new rules of economic governance at the European level , the concept of prudent fiscal policy becomes central . This is a reason for adopting a pro- active stance by continuing fiscal consolidation measures. That is why in this paper the authors present an analysis of public debt based on a correlated system of indicators.